A miR156-SPL module controls shade-induced inhibition of vascular cambium activity through cytokinin pathway in poplar - Hongbin Wei; Xingyue Xiao; Jiao Deng; Yi Li; Mengting Luo; Chengshan Zhang; Jieqiong Li; Jiayi Xu; Keming Luo (Cell Reports, 2025)
Summary: In natural forests and plantations, trees often encounter neighbor proximity that hinders wood production. However, the mechanisms by which shade regulates cambial activity during secondary growth remain elusive. Here, we show that high stand density and simulated shade (low R/FR ratios) inhibit cambial division and differentiation in Populus trees. Surprisingly, simulated shade increased miR156 levels, while downregulated miR156-regulated squamosa-promoter binding protein-like 16 (SPL16) and SPL23 in the phloem and cambium contributed to the suppression of cambial activity. Additionally, shade decreased bioactive cytokinin (CK) levels by suppressing the expression of CK biosynthesis genes IPT5a, IPT5b, and LOG1b in poplar stems. Further molecular and genetic analyses revealed that SPL16/23 directly activate IPT5s/LOG1b expression to promote cambial activity. These findings unveil a miR156-SPL16/23-IPT5/LOG1-CK signaling pathway that mediates the inhibition of cambial activity and xylem development under shade conditions, providing valuable targets for the genetic improvement of shade-tolerant trees.